2021
DOI: 10.1038/s41598-020-80758-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of kinase inhibitors binding modes with machine learning and reduced descriptor sets

Abstract: Protein kinases are receiving wide research interest, from drug perspective, due to their important roles in human body. Available kinase-inhibitor data, including crystallized structures, revealed many details about the mechanism of inhibition and binding modes. The understanding and analysis of these binding modes are expected to support the discovery of kinase-targeting drugs. The huge amounts of data made it possible to utilize computational techniques, including machine learning, to help in the discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…In detail, the class of descriptors ‘AlogP’, ‘Atom Count’, ‘Autocorrelation’, ‘Aromatic atoms count’, ‘Barysz matrix’, ‘BCUT’, ‘Burden matrix’, and ‘Atom type electrotopological state’ were present within each kinase-specific feature set. Moreover, this result was comparable with the outcome of Abdelbaky et al work, where the authors found that these descriptors reported a good ability to differentiate between the active and inactive classes within the kinase family 20 . This would suggest that these descriptors could well characterize the inhibitors of the examined kinases.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In detail, the class of descriptors ‘AlogP’, ‘Atom Count’, ‘Autocorrelation’, ‘Aromatic atoms count’, ‘Barysz matrix’, ‘BCUT’, ‘Burden matrix’, and ‘Atom type electrotopological state’ were present within each kinase-specific feature set. Moreover, this result was comparable with the outcome of Abdelbaky et al work, where the authors found that these descriptors reported a good ability to differentiate between the active and inactive classes within the kinase family 20 . This would suggest that these descriptors could well characterize the inhibitors of the examined kinases.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, in 2020 Miljković et al 18 applied different machine learning approaches to generate models on the basis of compounds with binding modes confirmed by X-ray crystallography for predicting different classes of kinase inhibitors (including types I, I1/2, and II as well as allosteric inhibitors). Similarly, in 2021 Abdelbaky et al 20 described the application of predictive models to discriminate between four binding modes: three allosteric inhibitor modes (I, II, I1/2) and one non-allosteric mode. The high accuracy rate of both works demonstrated that the new machine learning models have considerable potential for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The decoding network consists of LSTM layers. LSTM as a special RNN structure has proven successful and is widely used for modeling long-range dependencies in various previous studies [11,12,17,23]. The contribution of LSTM is recurrent connections, memory cell C t , and the self-parameterized and controlling gates, which essentially controls the flow of the state information.…”
Section: Convlstm-lstm Architecture For Energy Load Forecastingmentioning
confidence: 99%
“…However, these models have the limitation of dealing with the nonlinear nature of energy load data. To tackle this problem of nonlinearity, deep learning and machine learning have become very popular in recent times, inspired by stateof-the-art achievements in image classification [7], natural language processing [8], protein synthesis [9,10], drug discovery [11], and robotics [12]. Deep neural network architectures have the ability to learn complex data representations of the datasets, which alleviates the need for manual feature engineering and model design, considered to be a time-consuming and tidy job.…”
Section: Introductionmentioning
confidence: 99%
“…ML models have shown the ability to distinguish between multitarget and single-target kinase inhibitors [ 40 ] as well as robust performance in predicting different chemical classes of kinase inhibitors [ 41 ]. By representing kinase inhibitors as a large number of molecular descriptors, feature-based ML models can provide an accurate classification of kinase probes according to their binding modes [ 42 ].…”
Section: Introductionmentioning
confidence: 99%